Spinoza, a collection of critical essays - Grene, Marjorie, 1910-2009 (New York, Anchor Books, 1973)
This is another volume in the Modern Studies in Philosophy, a series of anthologies under the general editorship of Prof. Amelie Oksenberg Rorty, which present contemporary interpretations and evaluations of the works of major philosophers. This volume, consisting of a collection of papers by an impressive gallery of scholars, offers a plurality of perspectives on Spinoza. Each interpretation conflicts with some other; yet each illuminates some aspect of the subject. All the papers reflect the "tensions" and "conflicts" which make for very exciting and rewarding reading. Still the substantive puzzles remain and will continue to excite and fascinate successive generations of Spinoza's critics
Behind the geometrical method / H.A. Wolfson -- Experience in Spinoza's theory of knowledge / E.M. Curley -- Spinoza and language / David Savan -- Language and knowledge in Spinoza / G.H.R. Parkinson -- Spinoza's theory of knowledge in the ethics / Guttorm Fløistad -- Substance and its modes / H.F. Hallett -- Essence and the distinction of attributes in Spinoza's metaphysics / Alan Donagan -- Spinoza's letter on the infinite / Martial Gueroult -- The ontological argument in Spinoza ; The ontological argument in Spinoza : twenty years later / William A. Earle -- Eternity and sempiternity / Martha Kneale -- Spinoza's proof of immortality / Alan Donagan -- Spinoza and the theory of organism / Hans Jonas -- The two eyes of Spinoza / Leszek Kolakowski -- Spinoza and the idea of freedom / Stuart Hampshire -- Spinoza's account of imagination / R.G. Blair -- Action and passion : Spinoza's construction of a scientific psychology / Marx Wartofsky -- Spinoza's moral philosophy / E.M. Curley -- Spinoza and the political problem / Hilail Gildin
Includes bibliographical references (pages 389-390)
Keywords: Spinoza, Benedictus de, -- 1632-1677.